2008
DOI: 10.1182/blood-2008-05-158535
|View full text |Cite
|
Sign up to set email alerts
|

15-deoxy-Δ12,14-PGJ2 enhances platelet production from megakaryocytes

Abstract: Thrombocytopenia is a critical problem that occurs in many hematologic diseases, as well as after cancer therapy and radiation exposure. Platelet transfusion is the most commonly used therapy but has limitations of alloimmunization, availability, and expense. Thus, the development of safe, small, molecules to enhance platelet production would be advantageous for the treatment of thrombocytopenia. Herein, we report that an important lipid mediator and a peroxisome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 49 publications
3
67
0
Order By: Relevance
“…In this regard, it has recently been shown that the inhibition of PP1a by ROS leads to the constitutive activation of the PI3K/ AKT pathway in leukaemic cells. 33 In addition, it has been shown that ROS are also important for platelet release, 34 this points to the importance of ROS not only in triggering differentiation programmes but also in terminal platelet release from mature megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has recently been shown that the inhibition of PP1a by ROS leads to the constitutive activation of the PI3K/ AKT pathway in leukaemic cells. 33 In addition, it has been shown that ROS are also important for platelet release, 34 this points to the importance of ROS not only in triggering differentiation programmes but also in terminal platelet release from mature megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The megakaryoblastic cell line MEG-01, established from the bone marrow of a patient with chronic myelogenous leukemia, 30,31 represents a useful model for the study of human megakaryopoiesis. MEG-01 cells treated with 2-AG underwent differentiation, characterized by loss of rounded morphology and gaining of a spinous phenotype with extended cytoplasmic protrusions, and by expression of surface markers specific for late stages of megakaryocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…K-562 can be differentiated into various lineages depending of the inducer and MEG-01 can be differentiated toward the megakaryocytic pathway with several agents [18,19].…”
Section: Dac Treatment Induces Erythroid Differentiation Of K-562 Celmentioning
confidence: 99%
“…These results demonstrated that DAC induced only erythroid differentiation in K-562 based on the increase of GPA expression, the production of hemoglobin, and the absence of megakaryocytic markers. Finally, we completed this study by analyzing the particles derived from MEG-01, as this cell line is able to produce platelets similar in structure to freshly isolated human platelets [18]. DAC treatment of MEG-01 cells for 4 days caused an increase in platelets production ( Figure 3D, upper panel).…”
Section: Dac Treatment Induces Erythroid Differentiation Of K-562 Celmentioning
confidence: 99%